Best‐practice fisheries management associated with reduced stocks and changes in life histories. Issue 2 (29th October 2021) - McClanahan, Timothy R.; Friedlander, Alan M.; Wantiez, Laurent; Graham, Nicholas A. J.; Bruggemann, J. Henrich; Chabanet, Pascale; Oddenyo, Remy M.
Abstract: Current best‐practice policy recommendations for managing fish stocks are achieved by a mixture of maintaining modest fishing mortality (restricting effort, times and gear), marine reserve networks and not subsidizing unprofitable fisheries. A seldom evaluated question is how effective these proposed approaches are for maintaining all fish stocks and biodiversity elements in marine seascapes? Both recommended and unrecommended fishing practices fragment habitats and reduce metapopulation connectivity with potentially unexpected seascape‐level consequences. To better understand these outcomes, we pooled and evaluated fish community data into two seascape groupings for comparisons of biomass and life‐history characteristics. These were remote baseline reefs (>9 hr from regional cities and >4 hr from human habitation, n = 584 locations) and those emulating best‐practice seascapes (BPS, n = 140). BPS were a mix of high‐compliance marine reserves (fishable biomass = 892 ± 696 (± SD ) kg/ha, n = 95; >5 km 2 and >15 years of closure) and fished seascapes (478 ± 395 kg/ha, n = 45) that had biomass near the maximum sustained yield (MSY) estimates for coral reefs. The fish communities in the BPS locations differed considerably from the remote baseline by having 49% of the median and 32% of the mean biomass, smaller community‐weighted body sizes, and faster growth and mortality rates. Most of the declines were associated with high biomass taxa that included carnivorous jacks (Carangidae), snappers (Lutjanidae), groupers (Serranidae) and triggerfish (Balistidae), which were reduced to between 11% and 28% of the mean baseline. Surgeonfish (Acanthuridae) and parrotfish (Scarinae) were an exception in being reduced to only 48 and 53% of the baseline's mean biomass, respectively. As expected, community‐level body sizes and age values were larger and trophic level higher, while growth and mortality were lower in baselines than BPS seascapes. After evaluating the different environmental responses between seascapes and accounting for the largest geographic factor, longitude, we evaluated the community responses to 4 possible BPS planning scenarios. Biomass responses to age and trophic level and length at maturity were similar and predictable for the two seascapes. In contrast, growth and generation time responses differed between seascapes. Baselines had peak biomass patterns at intermediate values, whereas BPS displayed a declining influence of growth and a saturating response for generation time. Consequently, deviations between BPS and baselines indicate that current BPS proposals do not fully emulate the ecology of remote or wilderness locations. Therefore, wilderness will be a required management designation if the global fish communities are to be fully conserved.